Avaliação de diferentes temperaturas de branqueamento para abóbora (Cucurbita moschata Duch) minimamente processada - (:unkn) unknown (Universidade Federal do Pampa, 2014)
Pumpkins are grown all over Brazil and play an important role for human consumption. These are present in our diet since the formation of the first civilizations to the present day. The hybrid squash Tetsukabuto was presented, after being selected in Japan in mid 1940, arrived in Brazil in the 1960s and is also known as Japanese or Kabotiá pumpkin. The good performance of squash in Brazil owes its agronomic qualities such as hardiness, earliness, uniformity, high yield potential, organoleptic quality, including texture, flavor and reduced cooking time and prolonged post-harvest compared to other pumpkin cultivars. The conservation of minimally processed product depends on the product storage conditions, since the process considerably affects the structure of the plant. Targeting a later use of the product, and that this, provide a good quality and properties similar to those of fresh fruit, it is interesting to use the bleaching method as a viable alternative for better preservation. Given the above, this study was developed with the purpose of verifying the different efficiency bleaching temperatures pumpkin slices for life increase in airtight container. The treatments used bleaching temperatures of 70, 80 and 90 ° C and treatment control samples were not subjected to heat treatment. The experiment was conducted over a period of 21 days, and samples were taken at 0, 4, 7, 10, 15 and 21 days for mass loss analysis, moisture, soluble solids, pH, titratable acidity, color and texture. The results showed that heat treatments did not influence the improvement of the characteristics of pumpkins , but it was observed that the vacuum packaging is of great value for the storage of minimally processed. Were not perceived changes in their sensory characteristics, which continued until the 10th day of storage, and after this time an unpleasant odor has begun to be noticed. These results were important because there are few studies that studied the effect of bleaching on pumpkins, along with the use of vacuum packaging.
Keywords: Packaging; Vacuum; Conservation; Branqueamento; Embalagem à vácuo; Conservação; CNPQ::ENGENHARIAS